Мethods of control ecological safety of finishing materials - Yaremchuk, Larysa (Forestry, Forest, Paper and Woodworking Industry, 2024)
Мodern methods of creation of protective-decorative coverages are high-quality, proof, lasting tapes, ecological materials and technologies. Аn important aspect at the use of finishing materials are methods research of ecological safety.